Needle detachment in a slim and physically active child with insulin pump treatment. Issue 5 (23rd July 2015) - Moser, Christine; Maurer, Kathrin; Binder, Elisabeth; Meraner, Dagmar; Steichen, Elisabeth; Abt, Daniela; Freund‐Unsinn, Karin; Hofer, Sabine E.
Abstract : Insulin pump therapy (CSII) is well established in pediatric patients with type 1 diabetes. In childhood diabetes, insulin pump treatment shows considerable advantages such as fewer injections, increased flexibility, fewer hypoglycemic events and lower HbA1c levels. Side effects such as catheter obstruction, technical pump failure, and dermatological complications have been observed, but are rarely reported. The reported patient is a physically very active and slim 10‐year‐old boy with reduced subcutaneous fatty tissue. After strong muscular activity an accidental rupture of the infusion set and needle detachment occurred in October 2013. X‐ray and ultrasound imaging localized the needle in the musculus rectus femoris dexter. The needle was kept in situ and oral antibiotic treatment to prevent inflammatory reaction was prescribed. Repeated ultrasound measurements documented that the needles position had remained unchanged. Steel needle catheters (Sure‐T infusion set, 6 mm) positioned in a thin layer of subcutaneous fat tissue of the thigh, combined with intense sports activity can result in a needle rupture and penetration into the muscle. Careful monitoring provides an alternative to surgery and lowers the risk of muscular necrosis. Because of differences in the distribution of subcutaneous fat tissue, an individualized catheter selection is necessary in pump treatment for children and adolescents, requiring a variety of different catheter sets.